Proceedings of the European Physical Society Conference on High Energy Physics — PoS(EPS-HEP2017) 2018
DOI: 10.22323/1.314.0665
|View full text |Cite
|
Sign up to set email alerts
|

Quantum groups as fundamental symmetries

Abstract: The role of quantum groups and braid groups in the description of Standard Model particles is discussed. Some recent results on the use of the quantum group SU q (3) as a flavour symmetry are reviewed and a connection between two descriptions of Standard Model symmetries, one based on the normed division algebras and the other describing elementary matter as braided objects, is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There exist several curious structural similarities between recent braid-and Hurwitz algebraic descriptions of a single generation of fermions. Clifford algebras that are isomorphic to complex numbers and quaternions admit precisely those braid group representations from which the Helon model is contructed [19]. Furthermore, the ribbon braids representing fermions in that model coincide exactly with the states that span the minimal left ideals of the adjoint algebra of the complex octonions, shown by Furey to describe one generation of leptons and quarks with unbroken SU (3) C and U (1) EM symmetry.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There exist several curious structural similarities between recent braid-and Hurwitz algebraic descriptions of a single generation of fermions. Clifford algebras that are isomorphic to complex numbers and quaternions admit precisely those braid group representations from which the Helon model is contructed [19]. Furthermore, the ribbon braids representing fermions in that model coincide exactly with the states that span the minimal left ideals of the adjoint algebra of the complex octonions, shown by Furey to describe one generation of leptons and quarks with unbroken SU (3) C and U (1) EM symmetry.…”
Section: Discussionmentioning
confidence: 93%
“…Several curious structural similarities between the braid and Hurwitz algebra descriptions of SM fermions have recently been identified [19,20]. The complex numbers and quaternions contain representations of precisely the braid groups used to construct braided fermions in the Helon model.…”
Section: Introductionmentioning
confidence: 99%
“…More generally it is possible for any orientable braided 3-belt There are situations where writing a braided 3-belt in terms of braiding only rather than twisting only is advantageous. Together with the observation that Clifford algebras and normed division algebras contain representations of the circular Artin braid groups [7,8], it was recently shown that by removing the twists on ribbons in the Helon model braids, they can be written in a form such that they coincide with the basis states of the minimal left ideals of the complex octonions [9], which have been shown to transform as a single generation of leptons and quarks under the unbroken symmetries SU (3) c and U (1) em [10,11]. It is precisely because all the twisting can be exchanged for braiding that this identification between Helon braids and basis states of the minimal ideals of the complex octonions is possible.…”
Section: Introductionmentioning
confidence: 99%
“…For additional work related to this braid model and its connections with division algebras and Clifford algebras, the reader is referred to[12][13][14][15][16][17][18].…”
mentioning
confidence: 99%